Hereditary neuropathy with liability to pressure palsies (HNPP): Intrafamilial phenotypic variability and early childhood refusal to walk as the presenting symptom - Shani Karklinsky; Shir Kugler; Omer Bar-Yosef; Andreea Nissenkorn; Anat Grossman-Jonish; Irit Tirosh; Asaf Vivante; Ben Pode-Shakked (BMC, 2022)
Abstract Background Limping and/or refusal to walk is a common complaint in the setting of the pediatric department, with a widely diverse differential diagnosis. An unusual etiology, is that of a hereditary neuropathy. Hereditary neuropathy with liability to pressure palsies (HNPP) is a recurrent, episodic demyelinating neuropathy, most commonly caused by a 17p11.2 chromosomal deletion encompassing the PMP22 gene. Methods We pursued chromosomal microarray analysis (CMA) in multiple affected individuals of a single extended family, manifesting a range of phenotypic features consistent with HNPP. Results A 4.5 years-old boy presented for in-patient evaluation due to refusal to walk. Initial investigations including spine MRI and bone scan failed to yield a conclusive diagnosis. Following family history, which implied an autosomal dominant mode of inheritance, CMA was pursued and confirmed a 17p11.2 deletion in the proband consistent with HNPP. Importantly, following this diagnosis, four additional affected family members were demonstrated to harbor the deletion. Their variable phenotypic features, ranging from a prenatal diagnosis of a 6 months-old sibling, to recurrent paresthesias manifesting in the fourth decade of life, are discussed. Conclusions Our experience with the family reported herein demonstrates how a thorough anamnesis can lead to a rare genetic etiology with a favorable prognosis and prevent unnecessary investigations, and underscores HNPP as an uncommon diagnostic possibility in the limping child.